Expression of The Human Imagination and Creative Ability in Visual Form - Shabir, Sana (Journal of World Science, 2023)
Art is a visible manifestation of human creativity and imagination. A song, a sculpture, or a painting, for example, are all the products of human expressions, as are all other forms of art. They are typically admired for their beauty or emotional impact, much like in art. The human eye will appreciate the skill and beauty of an artist when they are able to depict reality in paintings in such a realistic manner. Therefore, it indicates that an artist is experimenting with realism when we talk about portraying subject matter so truly and without any artificiality. In the visual arts, realism refers to the precise representation of live forms, perspective, and the nuances of light and color. Viewing the work of a realistic artist using a conventional media and style is extremely uncommon in Pakistani contemporary art. Viewing works that explore only methods, drawing, composition, and accurately duplicating reality is even more uncommon. This chance came about as a result of Ali Azmat's recent solo exhibition at the Canvas Gallery in Karachi. Despite his past vivid and stunning work, a series of large-scale, realistic black and white portraits of women stood out.